Kajian Strategi Desain Terminal Bus Berkelanjutan Studi Kasus Terminal Induk di Kota Bekasi - Affan Maulana Yasin; Sri Yuliani (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Urban transportation is experiencing rapid growth in line with the increasing population, particularly in cities like Bekasi. Despite advancements in transportation modes in Bekasi, the Bekasi City Bus Terminal, classified as a Type A passenger terminal, still struggles to meet the mobility needs of its residents. The terminal faces various challenges, including traffic congestion, insufficient security and comfort in circulation, limited supporting facilities, poor services, and high environmental pollution levels. Therefore, this research aims to propose a redesign for the Bekasi City Bus Terminal, incorporating sustainable architectural principles. The research methodology involves a theoretical review using content analysis. The study results emphasize the necessity for design criteria that facilitate efficient circulation, transition spaces, and economic functionality in the bus terminal. Consideration of environmental conservation principles and building energy efficiency is crucial in this redesign process.